Preparation of porous nylon 6 fiber via electrospinning. Issue 5 (18th July 2014) - Zhang, Huimin; Zhang, Li; Jia, Qingxiu; Shi, Chaoming; Yang, Jian
<x xml:space="preserve">Abstract</x> Porous nylon‐6 fibers were obtained by electrospinning of ultra‐high molecular polyamide 6 (UHMW‐PA6). First, UHMW‐PA6/calcium formate composite nanofibers were prepared as precursors by electrospinning UHMW‐PA6 solutions containing different contents of calcium formate particles. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were used to examine the surface morphology and inner structure of composite nanofibers. It was found that calcium formate particles were distributed both inside and on the surface of nanofibers. Fourier transform infrared (FTIR), differential scanning calorimetry, and thermal gravimetric analysis (TGA) were used to study the structure and properties of these nanofibers. Then, porous UHMW‐PA6 nanofibers were obtained by soaking the electrospun web in water for 24 h, to remove calcium formate particles. The removal of calcium formate particles was confirmed using FTIR and TGA tests. SEM and TEM observations revealed the formation of porous structure in these nanofibers. In addition, CaCl2 was used instead of calcium formate to prepare the UHMW‐PA6 nanoporous fiber. POLYM. ENG. SCI., 55:1133–1141, 2015. © 2014 Society of Plastics Engineers